2015
DOI: 10.2323/jgam.61.82
|View full text |Cite
|
Sign up to set email alerts
|

Trichopolyn VI: a new peptaibol insecticidal compound discovered using a recombinant <i>Saccharomyces cerevisiae</i> screening system

Abstract: In the course of searching for insecticides from soil microorganisms, we found that a fermentation broth of the fungus, Trichoderma brevicompactum FKI-6324, produced Trichopolyn VI, a new peptaibol, which possessed significant insecticidal potential. Spectroscopic analysis showed the compound to be a new trichopolyn I derivative. This paper describes the isolation, structure elucidation and biological activity of trichopolyn VI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We recently established a screening method to discover substances that inhibit the function of the insect adenine nucleotide translocase (ANT), a protein that is evolutionarily conserved in vertebrate species and also known as the ADP/ATP carrier (AAC) in yeasts. 1,2) In this screening program, Saccharomyces cerevisiae lacking its AAC genes was complemented by the expression of insect or vertebrate ANT genes, and the inhibitory activities of substances for each ANT were easily monitored by investigating the survival of the transformants. Accordingly, this system enables us to explore a compound that is harmful to some insect species but not to vertebrates or other insects.…”
Section: Introductionmentioning
confidence: 99%
“…We recently established a screening method to discover substances that inhibit the function of the insect adenine nucleotide translocase (ANT), a protein that is evolutionarily conserved in vertebrate species and also known as the ADP/ATP carrier (AAC) in yeasts. 1,2) In this screening program, Saccharomyces cerevisiae lacking its AAC genes was complemented by the expression of insect or vertebrate ANT genes, and the inhibitory activities of substances for each ANT were easily monitored by investigating the survival of the transformants. Accordingly, this system enables us to explore a compound that is harmful to some insect species but not to vertebrates or other insects.…”
Section: Introductionmentioning
confidence: 99%
“…S. cerevisiae WB-12 pRS314YA2P, an endogenous AAC-disrupted and single-copy yeast shuttle vector pRS314YA2P-expressing strain (empty vector strain), was grown on a glucose-containing medium as the references. 5,6 Sterile filter discs impregnated with each compound solution (10 μl) were placed on the agar plate, and the plates were incubated at 30°C for 48 h. After incubation, the inhibition zones were measured.…”
Section: Yeast Growth Inhibition Assaymentioning
confidence: 99%
“…Thus we could obtain cultured broths that may affect mitochondrial function. 5,6 As a result, our screens showed that Aspergillus tamarii strain FKI-6817 produced a new compound (FKI-6817A; 1) that inhibited the growth of drug-sensitive BY25929 strain of S. cerevisiae. Compound 1 inhibited the growth of drug-sensitive budding yeast only in a glycerol-containing medium, and it elicited~50% inhibition of the ATP production in isolated mitochondria.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation